A world elsewhere - Quigley, S; Quigley, Sarah (1997)
When Charles Brasch died, in 1973, he specified that his private papers - his diaries, letters, and many of his manuscripts - be placed under embargo for thirty years after his death. The external details of his life were, by this time, well-known. He had become a high-profile figure in the field of New Zealand literature, through his critical writings, his role as 'patron', and particularly his twenty- year editorship of the periodical Landfall. Yet his reputation as a poet, although established, was neglected both then and now. His poetry is one of central relevance to a contemporary scene; as clearly as any, it reveals the difficulty of writing for, and about, a society which still laboured under the weight of a 'colonial' stigma. By tracing the movement from his juvenilia to his mature poetry, from his teenage years to adulthood, this study examines the effect of Brasch's personal development on his writing. Partly because of the embargo on his papers, partly because of his secretive nature, his private life has remained a shadow behind poetry which is itself often ambiguous; yet his creative progression was largely determined by the events of this life, both external and internal. Previously, little has been known or written about the decade and a half he spent in Europe. These were crucial years, both in shaping his editorial vision, and in the discovery of his own poetic voice. By means of personal interviews, and recourse to letters in private collections, his story is told: from his arrival in Oxford in 1927, to his final acceptance of New Zealand as his home, in 1945. The first chapter outlines the three years he spent at St John's College, and the general literary context in which he began to write. Chapter Two covers his brief foray into archaeology, and the resultant poetry and unpublished fiction. The importance of German literature - particularly that of Rilke - to his work becomes the focus of Chapter Three. As a direct result of this influence, the second half of the 1930s was dominated by his search for a voice, and a subject, of his own. Chapter Four details this struggle, and the first tentative New Zealand element in his work. A teaching job at Great Missenden - the subject of Chapter Five - temporarily distracted Brasch from developing this theme, yet sources reveal that the country of his birth was never far from his mind. Chapters Six and Seven deal with the effect on his poetry of the growing unease in Europe, the difficult split of allegiances to two hemispheres, and his subsequent commitment to England for the duration of the war. Throughout 1944-5, he became involved in script-writing, and the eighth and final chapter examines the extent of his success in this new genre. His return to New Zealand, late in 1945, marked the apparent beginning of a career which, nonetheless, had its origins in experiences half a world away.